Functional characterization of the G162R and D216H genetic variants of human CYP17A1. Issue 178 (April 2018) - Capper, C.P.; Liu, J.; McIntosh, L.R.; Larios, J.M.; Johnson, M.D.; Hollenberg, P.F.; Osawa, Y.; Auchus, R.J.; Rae, J.M.
Highlights: Two CYP17A1 variants, G162R and D216H, are functionally characterized. G162R variant exhibits decreased protein expression and a shortened half-life. G162R variant protein degradation is mediated by the ubiquitin-proteasome system. D216H variant demonstrates selective impairment of 16OH-progesterone synthesis. Graphical abstract: Abstract: Cytochrome P450 17A1 (CYP17A1) is a dual-function enzyme catalyzing reactions necessary for cortisol and androgen biosynthesis. CYP17A1 is a validated drug target for prostate cancer as CYP17A1 inhibition significantly reduces circulating androgens and improves survival in castration-resistant prostate cancer. Germline CYP17A1 genetic variants with altered CYP17A1 activity manifesting as various endocrinopathies are extremely rare; however, characterizing these variants provides critical insights into CYP17A1 protein structure and function. By querying the dbSNP online database and publically available data from the 1000 genomes project (http://browser.1000genomes.org ), we identified two CYP17A1 nonsynonymous genetic variants with unknown consequences for enzymatic activity and stability. We hypothesized that the resultant amino acid changes would alter CYP17A1 stability or activity. To test this hypothesis, we utilized a HEK-293T cell-based expression system to characterize the functional consequences of two CYP17A1 variants, D216H (rs200063521) and G162R (rs141821705). Cells transiently expressing the D216H variant demonstrate a selective impairment of 16α-hydroxyprogesterone synthesis by 2.1-fold compared to wild-type (WT) CYP17A1, while no effect on 17α-hydroxyprogesterone synthesis was observed. These data suggest that substrate orientations in the active site might be altered with this amino acid substitution. In contrast, the G162R substitution exhibits decreased CYP17A1 protein stability compared to WT with a near 70% reduction in protein levels as determined by immunoblot analysis. This variant is preferentially ubiquitinated and degraded prematurely, with an enzyme half-life calculated to be ∼2.5 h, and proteasome inhibitor treatment recovers G162R protein expression to WT levels. Together, these data provide new insights into CYP17A1 structure-function and stability mechanisms.